Consistent Plans - Goldman, Steven M. (Review of Economic Studies, 1980)
Journal Article Consistent Plans Get access Steven M. Goldman Steven M. Goldman University of California, Berkeley Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 47, Issue 3, April 1980, Pages 533–537, https://doi.org/10.2307/2297304 Published: 01 April 1980 Article history Received: 01 July 1978 Accepted: 01 April 1979 Published: 01 April 1980